Desenvolvimento de superfícies super-hidrofóbicas e oleofóbicas em liga de alumínio através da deposição de recobrimentos sol-gel - Andreia Rocha Canella Carneiro (2017)
In recent years, the development of superhydrophobic surfaces has been receiving increasing attention from academia to industry for the potential applications that can add to the surface of metals, glass, ceramics and polymers. In this work, the objective was to develop superhydrophobic coatings on ASTM 1200 H14 aluminum alloy. The surfaces were treated in order to produce a suitable rough structure followed by the deposition of coatings obtained from hydrophobic precursors. The substrates had surface roughness modified by etching in an oxidizing acid solution composed of FeCl3, HCl and H2O2, known as FHH, and received ORMOSIL coatings produced with the precursors 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES) and hexadecyltrimethoxysilane (HDTMS). All aluminum substrates, before and after chemical etching, were ultrasonically cleaned in sequence with acetone and deionized water for 5 min, and dried in a stream of hot air. The materials had their contact angles with water and oil measured using a tensiometer and their morphological and chemical characteristics evaluated through confocal microscopy, Scanning Electron Microscopy (SEM) coupled to X-ray Dispersive Energy Spectroscopy (EDS), X-ray excited photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectroscopy. The resulting surfaces were superhydrophobic, with mean contact angles with water greater than 150° and slip angle less than 5°. The rough surfaces covered with ORMOSIL of PFOTES also presented oleophobic properties, with mean contact values with mineral oil around 136°, being defined as amphiphobic. Deposits were also made using different ORMOSIL compositions obtained by mixing PFOTES and TEOS (tetraethyl orthosilicate) in order to reduce costs, since PFOTES is a relatively expensive compound without loss of amphiphic properties. The results revealed that the blends could significantly reduce process costs in the preparation of these surfaces.